The effect of social network diversity and social support on the thriving of healthcare workers - Kemal Kuşçu; Ozge Pasin; Merve Yalçınay -inan; Esra Bilir; Ozge Kılıc (Acta Medica Alanya)
Aim: The well-being of healthcare workers is a critical indicator in the provision of high-quality care. Although researchers have stressed the importance of social interactions and social support, scarce data exist about their effects on healthcare workers’ well-being. In this study, we aim to advance the research on the relationships between social network diversity (SND), social support, and thriving.Methods: In a cross-sectional design, an anonymous online link was shared among healthcare workers in a university hospital. The survey included questions on demographics, medical diseases, items from the social network index, the multidimensional perceived social support scale, and the brief and comprehensive inventories of thriving scales.Results: A total of 103 individuals participated in the study (median age, min-max=33 (18-57); male/female = 33/70). Men and women did not differ in SND, perceived social support, or thriving scores. The brief inventory of thriving demonstrated healthcare workers older than 38 years exhibited higher scores in thriving compared to those younger than 27 years (p=0.001). According to comprehensive inventory of thriving, belonging (p=0.032), skills (p=0.006), self-worth (p=0.048), meaning and purpose (p<0.001), optimism (p=0.009), life-satisfaction (p=0.012), and positive emotions (p=0.042) differed by age groups. SND (r=.56, p<0.001) and perceived social support (r=.53, p<0.001) were positively correlated with thriving. After adjusting for potential confounders, SND, perceived social support, and age accounted for 46% of the total effects on thriving.Conclusion: This study expands on the literature and provides evidence that by increasing the diversity of social networks and improving the quality and functionality of social support, a significant and positive impact on HCWs’ well-being may be achieved.